An on-line computer system for hospital bacteriology: description of its development and comments after five years' use. Issue 10 (October 1981) - Blair, JN; Brown, PP
Abstract : The development over several years of a computer system for hospital bacteriology reporting is described. The system was developed from a manual method to a punch-card batch processing system and finally to a real-time on-line system. The value of the system to the clinical departments and laboratory is discussed. Apart from minor defects the system has been of immense advantage to all who make use of its facilities.